INTERSEKSI HERMENEUTIK RICOEUR DENGAN HERMENEUTIK PENTAKOSTAL - Valentino Wariki (DIEGESIS: Jurnal Teologi Kharismatika, 2025)
This article explores Pentecostal hermeneutics as a distinctive Pentecostal approach to interpreting Scripture and actualizing it in the practice of life. In ecumenical life, how do Pentecostals combine Pentecostal hermeneutics as a hermeneutic method that is parallel to other theological products? By bringing together Paul Ricoeur's views on linguistic symbols and narratives, Pentecostal hermeneutics rejects the overly dominant historical-critical methodology. The results show that Pentecostal hermeneutics offers a dynamic and relevant reading model for the context of contemporary communities. The emphasis of Pentecostal hermeneutics is on the literalization of the text and the implementation of narrative criticism. Narrative criticism becomes a hermeneutical tool that is able to reach the features that are on the surface of the text and unite them in the vortex of interpretation. Pentecostal hermeneutics becomes an alternative for a simpler reading that can offer substantive and unsubstituted meaning from the context of its narrative. Abstrak Artikel ini mengeksplorasi hermeneutik Pentakostal sebagai pendekatan khas Pentakostal dalam menafsirkan Kitab Suci dan mengaktualisasikannya pada praktik kehidupan. Dalam kehidupan ekumenikal, bagaimana Pentakostal mempresentasikan hermeneutik Pentakostal sebagai suatu metode hermeneutik yang sejajar dengan produk teologis lainnya? Dengan mempertemukan pandangan Paul Ricoeur mengenai simbol-simbol linguistik dan narasi, hermeneutik Pentakostal menolak metodologi historis-kritis yang terlampau dominan. Hasilnya memperlihatkan bahwa hermeneutik Pentakostal menawarkan model pembacaan yang dinamis dan relevan dengan konteks komunitas kontemporer. Penekanan hermeneutik Pentakostal ada pada literalisasi teks dan implementasi kritik naratif. Kritik naratif menjadi alat hermeneutis yang mampu menjangkau fitur-fitur yang berada di permukaan teks dan menyatukannya dalam pusaran tafsir. Hermeneutik Pentakostal menjadi alternatif guna pembacaan yang lebih sederhana yang dapat menawarkan makna yang substantif dan tidak tersubtitusi dari konteks narasinya.